New House, New Furniture, New Room: Children’s Pandemic Landscapes of Care in Chile - Susana Cortés-Morales; Inés Figueroa; Ana Vergara del Solar; Paola Jirón (Urban Planning)
Standing at the intersection between geographies of care and children’s geographies, we present three ethnographic stories (emerging from three ethnographic studies) through which we argue that, as a result of pandemic confinement in Chile, children’s places within their landscapes of care shifted in a twofold sense: First, given the de-mobilisation and spatial concentration of spaces of care at home, children’s place became closer to adults,’ suspending the usual spatial segregation that separates them. And second, in tandem with this new proximity that we refer to as in-person family relationships, new possibilities for the involvement of children in family care practices emerged. This rearrangement of children’s places within landscapes of care brings to the fore two interrelated aspects of family care from children’s perspective. First, the kind and amount of in-person family time spent in a shared space in “normal” times was not enough from the perspective of children’s needs and interests. And second, even though children are usually seen as subjects of care, they are people who care for others and who are able to take on more caring responsibilities than the ones that they usually are expected to.